Analisis Karakteristik Nelayan Tradisional Berdasar Jenis dan Klasifikasi Nelayan, Kelompok Kerja, Jenis Perairan, Teknologi, Aspek Keterampilan Profesi, Sistem Navigasi dan Komunikasi - Sabihaini Sabihaini; Awang Hendrianto Pratomo; Heru Cahya Rustamaji; Sudaryatie Sudaryatie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
The purpose of this research is to map the types of fish and classification of fishermen. The types and classification categories of fishermen observed are based on fisherman classification, ownership, work group classification, waters, technology, skills, navigation systems and communication systems used by fishermen. The map results are used to design a prototype of fishermen navigation systems for appropriate technology products. The results of the mapping show that the classification of Depok Beach Fishermen by Working Group is divided into individual fishermen groups, joint business group fishermen, and company fishermen; classification of fishermen based on water types, including coastal fishermen, fishermen without boats, and coastal fishermen and fishermen without boats; classification of fishermen based on technology, including traditional fishermen; classification of fishermen based on aspects of professional skills, formal fishermen and non-formal fishermen; navigation system, a navigation system that is used by combining nature, feelings, and instincts; The communication system used by fishermen is a hp-receiver which is also reliable for friends.